2016
DOI: 10.1088/1475-7516/2016/12/036
|View full text |Cite
|
Sign up to set email alerts
|

Domain walls and gravitational waves in the Standard Model

Abstract: We study domain walls which can be created in the Standard Model under the assumption that it is valid up to very high energy scales. We focus on domain walls interpolating between the physical electroweak vacuum and the global minimum appearing at very high field strengths. The creation of the network which ends up in the electroweak vacuum percolating through the Universe is not as difficult to obtain as one may expect, although it requires certain tuning of initial conditions. Our numerical simulations conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 32 publications
6
46
0
Order By: Relevance
“…Extrapolating previous results for the case of the zero temperature effective potential described in [28,29] we can expect that Higgs field configurations from probability distributions with σ < 1.2h max and θ = 0 should evolve toward the electroweak vacuum. Thus, we can estimate the range of temperatures for which end point of evolution of our network networks will be cosmologically acceptable.…”
Section: Initial Conditions For Simulationssupporting
confidence: 72%
See 1 more Smart Citation
“…Extrapolating previous results for the case of the zero temperature effective potential described in [28,29] we can expect that Higgs field configurations from probability distributions with σ < 1.2h max and θ = 0 should evolve toward the electroweak vacuum. Thus, we can estimate the range of temperatures for which end point of evolution of our network networks will be cosmologically acceptable.…”
Section: Initial Conditions For Simulationssupporting
confidence: 72%
“…In our two previous papers [28,29] we investigated the evolution of domain walls of the Higgs field in the SM and its extensions. In our attempt to understand the role of the networks of Higgs domain walls in the history of the Universe we have been working under simplifying assumption that SM particles present in early Universe had negligible effect on the dynamics of the expectation value of the Higgs field.…”
Section: Thermal Corrections To Sm Effective Potentialmentioning
confidence: 99%
“…In view of the forthcoming experimental studies of relict gravitational waves, this subject attracted attention recently [8][9][10][11][12][13][14], for a review see [15]. Particular models considered include the hybrid inflation [9], the standard model extended to the very early universe [14], the Higgs model [11], the next-to-minimal supersymmetric standard model [12] and some other. The results are based on numerical simulations of creation and annihilation of DW with account for gravitational radiation computed via the correlation functions of the energy-momentum tensors.…”
Section: Jhep01(2018)120mentioning
confidence: 99%
“…[67]. Contrary to the above discussions, it was concluded that the amplitude of GWs is too small to be observed in the planned detectors.…”
Section: Standard Model Higgs Fieldmentioning
confidence: 69%
“…However, it should be noted that the scenario considered in Ref. [67] is different from the above scenario in the sense that the high-scale minimum is located at a superplanckian value and that two minima are non-degenerate. In such a case, domain walls do not enter into the scaling regime and collapse soon after the formation, leading to the small amplitude of relic GWs.…”
Section: Standard Model Higgs Fieldmentioning
confidence: 90%